Globalization And Its Influence On Social Inequalities And Poverty Alleviation In Indonesia - Narisha Anindita; Viola Syukrina E Janrosl (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of e-money usage and financial literacy on the consumption behavior of accounting students in Batam City. E-money as a digital payment method has become increasingly popular among the younger generation, while financial literacy plays an important role in effective personal financial management. The study uses primary data collected from questionnaires distributed to 97 accounting students in several universities in Batam, as well as secondary data from interviews with 10 accounting students regarding e-money and financial literacy. The results show a positive correlation between high financial literacy and wise financial management, which in turn influences students' consumption behavior. Additionally, the use of e-money plays a significant role in facilitating transactions and changing consumption patterns. Simultaneously, all three variables have a significant impact with a coefficient of determination (R²) of 38.5%. The findings are expected to provide insights for relevant stakeholders in designing more effective financial education programs and promoting the use of e-money among students.